دور المزيج الترويجي في تحقيق الحصة السوقية: دراسة حالة شركة سكر كنانة - حسابو احمد حسابو أدم (White Nile Journal for Studies and Research, 2021)
This paper aimed at recognizing the role of promotion mix for ascertaining the market share for Kenana Sugar Company, and it was hypothesized there were statistical relationship between marketing mix elements & ascertaining market share. The researcher used descriptive & historical methods, in addition to the Statistical Package for Social Sciences (SPSS). This paper concluded to various findings, such as: perusal suitable promotion evolution will lead the Kenana to ascertain market share, the styles of expenditures of the clients in the targeted markets, also motivated Kenana to ascertain the market share. The most focused recommendations were; enlarging advertisement campaigns through the possible media for attracting more clients & consumers, and to recognize about their tendency & attitudes, in order to meet their interests & needs, also it is so necessary to assign promotional strategic for products marketing & and to ascertain sustainable market share. Key words: sales activation, market share, clients’ loyalty, promotional efforts & personal promotion mix elements